A Randomized Controlled Study on the Timing of Furosemide for Reducing Operative Hysteroscopy Intravascular Absorption Syndrome (OHIAS) during Hysteroscopic Leiomyoma Surgery - Xia Cao; Xu Ding; Huihui Sun; Xinyuan Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: The purpose of this study was to compare the effect of pre- and post-treatment furosemide on reducing intravascular absorption syndrome in complex hysteroscopic leiomyoma surgery. Methods: This randomized controlled study enrolled 62 patients who underwent hysteroscopic leiomyoma surgery in Fuxing Hospital, Capital Medical University. Patients were randomly allocated to pre- and post-treatment furosemide groups. Information on patient age, body mass index, sum of the three diameters of the uterus, sum of diameter of submucosal myoma, and intimal thickness were recorded. The mean arterial pressure and heart rate were recorded at entry to the operating room, after anesthesia induction, at the end of operation, and after laryngeal mask pulled out. The duration of anesthesia, recovery time after withdrawal of anesthetic drug, amount of sufentanil, amount of propofol, amount of uterine perfusion fluid, the amount of perfusion fluid flowing out, the actual amount of fluid intake, the proportion of pulmonary diffuse B-line in perioperative period, and uterine perfusion pressure during operation were also recorded, together with postoperative adverse reactions (drowsiness, nausea, vomiting, chills). Results: No significant differences were observed between the pre- and post-treatment groups in terms of patient age, body mass index, sum of the three diameters of the uterus, sum of diameter of submucosal myoma, and intimal thickness. The mean arterial pressure and heart rate at the four different time points were not significantly different between the two groups, nor were there any significant differences in the duration of anesthesia, the amount of sufentanil, the amount of propofol, the amount of intrauterine perfusion fluid, the amount of perfusion fluid flowing out, the actual amount of fluid intake, the intrauterine perfusion pressure, or the incidence of postoperative drowsiness, nausea and vomiting. However, pre-treatment with furosemide was associated with a significantly reduced recovery time (p = 0.037) and incidence of postoperative chills (p = 0.032) compared to the post-treatment group. Furosemide significantly reduces the number of B-lines. Conclusions: Furosemide preconditioning can reduce the recovery time and occurrence of postoperative chills, both of which are conducive to better postoperative recovery. Clinical Trial Registration: The study was registered at https://www.chictr.org.cn (registration number ChiCTR2200062840).